Quasi-homeomorphisms between ordered topological spaces: Abdelwaheb Mhemdi - Team, Support (Thai Journal of Mathematics, 2022)
In this paper, we introduce the notion of quasi-homeomorphism in the category of ordered topological spaces. Some related results are given. We give also some relation of quasi-homeomorphisms with T_0-ordered topological spaces.